PROBABILITAS PERUBAHAN TUTUPAN LAHAN BERDASARKAN KEBERADAAN LOKASI WISATA DI WILAYAH PESISIR SARBAGITA - Wayan Damar Windu Kurniawan (Sustainable, Planning and Culture (SPACE) : Jurnal Perencanaan Wilayah dan Kota, 2019)
he availability of land for fulfillment of space in the Sarbagita coastal area is increasingly limited. This iscaused by the rapid development of tourism in the Sarbagita coastal region, which can eliminate a large portion ofproductive agricultural land. This study specifically examines the probability value of land cover change, especially fromnon-built up area to built up area, in the Sarbagita coastal area until 2030. Calculation of the probability of land coverchange is done through fuzzy set logic which is assessed based on 1 main parameter, namely tourist location and 2supporting parameters, namely accessibility and service facilities, and also limiting factors. The value of the fuzzymembership is taken from Landsat images from 1995 to 2015. The results show the probability of changes in land coverhas values from 0 (very low) to 0.97 (very high). This means that there is no one land that must change (value 1) fromnon-built land to being built. The probability of a high land cover change tends to follow the road network pattern.